Friday

April 18, 2014

April 18, 2014

Posted by **jame** on Sunday, December 5, 2010 at 2:56pm.

- algebra -
**Jennifer**, Sunday, December 5, 2010 at 10:42pm1-5=-4m^2

-4=-4m^2

Dividing by -4 on both sides

we have:

(-4)/(-4)=(-4m^2)/(-4)

1=m^2

Take the square root of both

sides we have:

sqrt(1)=sqrt(m^2)

1=m or

m=1

Hope this helps.

**Related Questions**

Algebra - I had to solve the function g of f where f is x^2+1 and g is sq. root ...

Algebra - I had to solve 2x^2-x-1 using the quad. formula. I got it down to (1...

algebra 2 - I'm stuck on this one problem. The directions say: Solve the ...

Intermediate Algebra - Solve x^2 + 3x + 3 = 0 -1 +- sq.rt 1-4 (1)(3) -1 +- sq.rt...

Algebra - Which radical expression is in simplified form? a.11y/sq rt 3 b.sq rt ...

college algebra - Solve: sq root of (x+1) minus 3 = sq root of (x+4) when I ...

algebra - How would you solve this? I don't even know how to begin this... I ...

Math - 1) Solve equation 3r+5 _____ + 2 = 2r to find the value of r? 2 A. 2 1/7 ...

Solving an Equation in one variale - If x belongs Z, Solve the equation sq.rt(1...

algebra 2 - Simplify #54 -18c * -2c(cubed) #62 yi-16y(sq)+ 16y(sq) - y(...